KINERJA KEPALA DESA DALAM PELAKSANAAN PEMBANGUNAN DESA DI DESA TOLOK SATU KECAMATAN TOMPASO - ONIBALA, MAYA; Kiyai, Burhanuddin; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACTThe objective of this research is to know the performance of Village Head of one Tolok in the implementation of deda development. The study was conducted from april to june 2017. The method used is qualitative method where a type that providcs a description or description of facts collected in the field relate closely to the object of research, the data source used is primary data and secon dary data and informan are involved are people who can provide information about the situation and condition of the research background that is a total of 10 informants namely the village head 1 orang, village secretary 1 person, guard head 3 person, and the community as many as 5 person. The results showed that the Village Head in carrying out its performance in the implementation of development seen from the quantity of work, quality of work, job knowledge, creativity, cooperation, initiative, dependability, personal qualities it?s goob enough to see from some successful development programs. Referring to the findings of this study, so in view need to give some suggestion as solution of problem solving in this research, as follows : (1) in order to ensure the realization of all village development plans/programs, especially on one tiered villages, it is recommended that at the completion prepation and placement of village development programs/ plans, village heads at time also need to conduct direct socialization to the community to invite the community to participate actively in the process of implementation of village development. So that people can know the importance of community participation in the implementation of development. (2) to increase awareness and high participation of the community in the village development process, it is advisable for the village head and village officials to explore and understand the urgent needs of the community in the planning and implementation of the development program.Keywords: Performance of Village